2017
DOI: 10.1542/peds.2017-0671
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Intensity of End-of-Life Care for Children With Cancer

Abstract: Nearly two-thirds of children who died of cancer experienced intense end-of-life care. Further research needs to determine if these rates and disparities are consistent with patient and/or family goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
99
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 37 publications
11
99
3
1
Order By: Relevance
“…To our knowledge, population‐based studies have been performed on children, adolescents, and young adults in only 4 countries: 1 in Canada, 1 in Korea, 2 in Taiwan, and 3 in the United States . Exploring EOL care in children, adolescents, and young adult in other countries and health care systems using national medical administrative databases may provide additional information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, population‐based studies have been performed on children, adolescents, and young adults in only 4 countries: 1 in Canada, 1 in Korea, 2 in Taiwan, and 3 in the United States . Exploring EOL care in children, adolescents, and young adult in other countries and health care systems using national medical administrative databases may provide additional information.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, population-based studies have been performed on children, adolescents, and young adults in only 4 countries: 1 in Canada, 15 1 in Korea, 16 2 in Taiwan, 17,18 and 3 in the United States. 11,19,20 Exploring EOL care in children, adolescents, and young adult in other countries and health care systems using national medical administrative Cancer July 1, 2019 databases may provide additional information. The French Health System may offer an interesting approach, as its universal health coverage guarantees access to care regardless of cost 21 and may facilitate access to EOL and palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they are more likely to receive delayed care and to experience unmet care and coordination needs (Nageswaran, Silver, & Stein, ). Furthermore, there may be socioeconomic disparities in the provision of health care for children with complex healthcare needs, which has an immediate impact on their quality of life (Didsbury et al., ; Johnston et al., ).…”
mentioning
confidence: 99%
“…8 However, previous research has also identified differences in treatment utilization across racial-ethnic and socioeconomics groups. [11][12][13] This may be compounded when therapies are novel, intensive, or expensive.…”
Section: Discussionmentioning
confidence: 99%